Saberes tradicionais e tabus entre mulheres ribeirinhas do Lago Amanã (AM) e quilombolas do Vale do Ribeira (SP) - Souza, Tamires de Lima (2021)
Food prohibitions involve cultural, social, and biological factors that impact the way individuals interact with natural resources in their environment. This dissertation aimed to understand how food taboos and restrictions are structured among ribeirinhas women of Amanã Lake (AM) and quilombolas of Ribeira Valley (SP). To this end, we have adopted an ethnographic-oriented ethnoecological approach in the field. During the fieldwork, we combined the use of participant observation, informal conversations, and semi-structured interviews. We have documented 97 food items under restriction, 56 among quilombolas, and 51 items cited by the ribeirinhas. Hot-cold/dry-wet syndrome was prevalent in the Ribeira Valley while the system of reima dominated the reports in the Amanã Lake. Making use of categories of purity and ambiguity proposed by Mary Douglas we could access the classificatory (or epistemic) dimension of items subject to interdictions. Based on Philippe Descola’s theory of analogism, we infer the ontological foundations of local beliefs in danger related to taboos in the two ethnographic contexts. In this perspective, we could observe relevant similarities between the two areas. In sum, the comparative fashion of this study points out some regularities with which beliefs in taboos can manifest in the Brazilian rural context in general.